On the Meaning/s of טמאת האדם in the Damascus Document: A Textual Excavation of CD XII, 15B-17A - Mizzi, Dennis (Revue de Qumran, 2016)
For a passage that comprises a mere two lines, CD XII, 15b-17a has generated a considerable amount of scholarly literature. Its text has been amended a number of times, and its history of interpretation is characterized by a fluctuation of ideas. Depending on how it is read, this passage could potentially shed light on issues such as corpse impurity, the (im)purity of materials, and terminology pertaining to ritual uncleanness in the Damascus Document and the wider movement in which it was read. This paper analyses in detail the philological, literary, and socio-cultural context of CD XII, 15b-17a, with a particular focus on the meaning/s of the designation טמאת האדם, which is the key to understanding this passage. The conclusion is that, most likely, טמאת האדם refers to ritual impurity in general and not specifically to corpse impurity, the latter being the interpretation of the majority of commentators. In the process, this analysis contributes, by way of a practical example, a conceptual framework pertinent to lexicographical work on the Dead Sea Scrolls and highlights the challenges we must deal with when we attempt to explicate the meaning of certain lexical items in the Scrolls.